THE RELATIONSHIP BETWEEN LEARNING CYLINES, LEARNING CREATIVITY AND THE ENVIRONMENT OF FAMILY STUDENT WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VII OF SMP - Fatma Indriyani Nikmah; Uus Kusdinar (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
Low student learning outcomes associated with many factors. The relationship between learning cylinders, learning creativity, and family students' environment is possibly related to learning outcomes. This research aims to determine the presence or absence of positive and significant relationships between learning cylinders, learning creativity, and the family student's environment to Mathematics Learning Outcomes in Students Class VII of SMP Negeri 15 Yogyakarta in Even Semester in Academic Year of 2016/2017. The population in this research was the students of VII of SMP Negeri 15 Yogyakarta in the academic year of 2016/2017, consisted of class  VII A, VII B, VII C, VII D, VII E, VII F, VII G, VII H, VII I, VII J, totaling 345 students. Samples were taken from VII B as the research sample class and with the random sampling technique. The writer uses a questionnaire method to collect the data of learning cylinders, learning creativity, and the environment of family student and test method to get the resulting learning of math. The research instrument: validity test, different power test, and reliability test. Test requirement analysis includes a test of normality, linearity test, and the test of independence. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed that there was a positive and significant relationship between learning cylinders, learning creativity, and the environment of the family student with mathematics learning outcomes in students class VII of SMP Negeri 15 Yogyakarta in Even Semester in Academic Year of 2016/2017. It is showed by Fcount  Ftable is  with 8 and  with , with relative contribution , relative contribution  and relative contribution , effective contribution  dan effective contribution .